Pemberian Dispensasi Kawin Dibawah Umur Oleh Hakim Pasca Perubahan Undang-Undang Perkawinan - Muh Nizar Zulmi; Nur Mohamad Kasim; Dolot Alhasni Bakung (Lembaga Pengembangan Kinerja Dosen, 2024)
The granting of marriage dispensation by judges experienced a discourse from the age of marriage, which originally occurred because of the age difference between men and women, which caused family conditions that were not solid, with the younger age of women causing marriage to look more discriminating against women in the purpose of marriage. Then it changed to a regulation that equalized the age limit for marriage for both men and women. In the treatment of deviations from the rules of marriage age, it is also emphasized that there is equal treatment. However, this cannot limit the judges' ability to render judgments. The examination of marriage dispensation must be carried out thoroughly, so the focus of this study is on how the dynamics present in each decision by judges need to be analyzed. The research method is a study of normative law related to the provisions of the marriage dispensation. The analysis is carried out with the theory of judicial power, which includes legal justice, legal certainty, and legal expediency. The results showed that every judge's decision is affected by the disparity of the judgment on the granting of marriage dispensation when the judge does not examine all the offenses of the application for dispensation in the search for the application for dispensation, which becomes the basis for the judge to consider the decision. So that stigma for urgent reasons does not become unclear and clear. Therefore, every trial must systematically follow the judicial process in order to realize the purpose of marriage